Kepribadian Tokoh Utama dalam Novel Guru Aini Karya Andrea Hirata: Kajian Psikologi Sastra Alfred Adler - Imas Juidah; Agus Nasihin; Ade Reza (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This study aims to describe the personality of the main character in the novel Guru Aini by Andrea Hirata based on Alfred Adler's theory. This research is a qualitative descriptive research. The data in this study are words, sentences, and quotes contained in the novel Guru Aini by Andrea Hirata. Meanwhile, the data source in this research is the novel Guru Aini by Andrea Hirata. The data collection technique in this study was a reading and note-taking technique. The results of this study indicate that there are six personality theories in the main character, namely the character of Desi Istiqomah. First, the struggle for success or superiority contained in the character Desi. Second, subjective observations found in Desi's character. Third, the unity of personality contained in the character Desi. Fourth, the social interest found in Desi's character is a sense of caring for poor children by giving most of her salary to buy stationery and other necessities. Fifth, the lifestyle found in Desi's character is to have a simple lifestyle. Sixth, the creative strength contained in Desi's character is that he always has ideas to give mathematics lessons to his students